1965
DOI: 10.1055/s-0038-1654874
|View full text |Cite
|
Sign up to set email alerts
|

A Congenital Inhibitor against Factor IX

Abstract: SummaryA new congenital hemorrhagic diathesis, which is due to the presence of a circulating inhibitor against factor IX, simulating a hemophilia B, is described. It is demonstrated, that the inhibitor becomes much less efficient when the factor VUI-concentration decreases. A hypothesis is given which should explain the role of factor VIII in the inhibition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

1967
1967
1973
1973

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
0
1
Order By: Relevance
“…Brown, Diamant, Galbraith and Wilson (1963) reported a case of familial haemorrhagic diathesis resulting from an antithrombin believed to be different from the normal antithrombins previously described. A case of a congenital inhibitor against Factor IX was reported by Stocker (1965). None of these cases resembles ours.…”
Section: Discussionsupporting
confidence: 39%
“…Brown, Diamant, Galbraith and Wilson (1963) reported a case of familial haemorrhagic diathesis resulting from an antithrombin believed to be different from the normal antithrombins previously described. A case of a congenital inhibitor against Factor IX was reported by Stocker (1965). None of these cases resembles ours.…”
Section: Discussionsupporting
confidence: 39%
“…This sporadic occurrence has suggested that there may be a predisposition to their development, and the studies of the kindred reported here suggest a familial predisposition although others have not noted an incrcased familial incidence (Margolius et al, 1961;Bidwell, 1969;Strauss, 1969). Stocker (1965) has reported a factor-IX inhibitor which appeared to be familial but in his cases, unlike ours, the inhibitor appeared to be an abnormal factor IX and was present at birth. As noted, the inhibitor reported here was acquired and did not behave like factor IX since it was not adsorbable by aluminium hydroxide, was stable at 56°C for 30 min and was identified as an IgG globulin.…”
Section: Discussioncontrasting
confidence: 59%